Analisis Pengoptimalan Cycle Time Distribusi Semen: Perbandingan Satu dan Dua Kompresor di PT. X - Nugroho, Tito Dwi; Waluyo, Minto (Fakultas Teknik Universitas Tulang Bawang, 2025)
Distribution efficiency in the cement industry is a key factor that influences the sustainability of operations and company competitiveness. One critical aspect is managing distribution cycle time, which involves the process of loading cement from the factory to the ship. This research was conducted at PT. X to analyze cycle time optimization in cement distribution using discrete simulation methods. This research is the importance of reducing cycle time to avoid delivery delays which can result in fines (demurrage) and operational losses. The simulation results show that using one compressor requires an average of 108 minutes per trip, so that to complete 5 trips per trailer it takes a total of around 11.3 hours. While this duration still allows for the delivery target of 1,800 tons in 12 hours to be achieved, this approach leaves little room to overcome potential operational obstacles, such as technical glitches or delays, thereby increasing the risk of late fines. As a solution, the addition of one compressor has been proven to reduce loading time to 54 minutes per trip, reducing the total time for 5 trips to only 6.8 hours, providing significant efficiency and increasing operational reliability. This research concludes that adding a compressor can significantly reduce the risk of delays, increase efficiency and support the sustainability of company operations. Keywords : Cycle Time, Distribution, Discrete Simulation, Loading